Individual ingredients of NP-101 (Thymoquinone formula) inhibit SARS-CoV-2 pseudovirus infection - Maen, Abdelrahim; Gok Yavuz, Betul; Mohamed, Yehia I.; Esmail, Abdullah; Lu, Jianming; Mohamed, Amr; Azmi, Asfar S.; Kaseb, Mohamed; Kasseb, Osama; Li, Dan; Gocio, Michelle; Kocak, Mehmet; et al. (Frontiers in Pharmacology, 2024)
Thymoquinone TQ, an active ingredient of Nigella Sativa, has been shown to inhibit COVID-19 symptoms in clinical trials. Thymoquinone Formulation (TQF or NP-101) is developed as a novel enteric-coated medication derivative from Nigella Sativa. TQF consists of TQ with a favorable concentration and fatty acids, including palmitic, oleic, and linoleic acids. In this study, we aimed to investigate the roles of individual ingredients of TQF on infection of SARS-CoV-2 variants in-vitro, by utilizing Murine Leukemia Virus (MLV) based pseudovirus particles. We demonstrated that NP-101, TQ, and other individual ingredients, including oleic, linoleic, and palmitic acids inhibited SARS-CoV-2 infection in the MLV-based pseudovirus model. A large, randomized phase 2 study of NP-101 is planned in outpatient COVID-19 patients.